Withdrawal of Processed Food And Cosmetic Products Without Bpom Distribution Permits - Shelomita Putri Amelia; Dwi Desi Yayi Tarina (Dinasti Research, 2025)
The circulation of processed foods and cosmetics without distribution permits from the Food and Drug Supervisory Agency (BPOM) continues to increase in line with high market demand. This situation poses problems because products that have not undergone an evaluation process may contain hazardous ingredients and do not meet established safety and quality standards. This study aims to analyze the mechanism for recalling unlicensed foreign products and the legal implications of recalling unlicensed processed food and cosmetic products from abroad. Normative legal research using a legislative, case, and conceptual approach is the methodology employed. Research data was obtained through a literature study using primary, secondary, and tertiary legal materials. The study's findings demonstrate that BPOM uses pre-market and post-market oversight as part of a systematic supervisory mechanism. Product recalls are carried out in layers, starting from administrative sanctions to legal action in the event of repeated violations. The legal implications can take the form of technical guidance from BPOM and/or administrative sanctions such as warnings. In conclusion, BPOM's mechanism for recalling products without distribution permits emphasizes the importance of business actors' compliance with licensing regulations.